The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/ccm.0b013e31817b86e3
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide binding protein in a surgical intensive care unit: A marker of sepsis?*

Abstract: In the surgical ICU, LBP moderately discriminated patients without infection from patients with severe sepsis but not from patients with sepsis without organ dysfunction. LBP concentrations did not distinguish between gram-positive and gram-negative infections. The correlation of LBP concentrations with disease severity and outcome is weak compared with other markers and its use as a biomarker is not warranted in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 31 publications
(28 reference statements)
9
65
0
6
Order By: Relevance
“…LBP levels increase in patients with septicemia from Gram-positive, Gram-negative and fungal infections [14][15][16][17][18][19]. This molecule is constitutively synthesized in hepatocytes after being induced by IL-1 and IL-6 during the acute phase response.…”
Section: Discussionmentioning
confidence: 99%
“…LBP levels increase in patients with septicemia from Gram-positive, Gram-negative and fungal infections [14][15][16][17][18][19]. This molecule is constitutively synthesized in hepatocytes after being induced by IL-1 and IL-6 during the acute phase response.…”
Section: Discussionmentioning
confidence: 99%
“…The acutephase protein LBP is a 60-kDa serum glycosylated protein, forming high-affinity complexes with bacterial endotoxins (lipopolysaccharide), functioning as an opsonin, that is produced and secreted by hepatocytes. The reference limit of LBP in healthy individuals is less than 10 μg/ml [83][84][85]. The results of this study showed increased sIL-2R and LBP postmortem serum levels over the clinical reference limits in sepsis-related fatalities, suggesting that these markers could be an appropriate diagnostic tool, in combination with other biochemical markers, in the postmortem diagnosis of sepsis in forensic autopsy practice.…”
Section: Acute-phase Proteins and Cytokinesmentioning
confidence: 71%
“…Keiner ist als alleiniger laborchemischer Parameter geeignet, die Diagnose "Sepsis" zu stellen. Gleichwohl kann die Bestimmung hilfreich sein, um früher als allein klinisch die richtige Diagnose zu stellen (IL-6), um zwischen bakterieller Sepsis und SIRS zu differenzieren (PCT, LBP), um die antibiotische Therapiedauer zu verkürzen (PCT) oder für das Monitoring der Entzündungsaktivi-tät im längeren Verlauf (CRP) [7][8][9][10][11][12][13][14]. Am besten etabliert ist dabei das PCT, das sogar ein Kandidat als "offizielles" Definitionskriterium der Sepsis ist [15].…”
unclassified
“…Laborwerte wie das CRP helfen nur im Verlauf. Routinescreening mit PCT oder LBP konnte die Erwartungen nicht ganz erfüllen und ist ausgesprochen kostspielig [10]. Das Entscheidende ist ein hoher Grad an Aufmerksamkeit und das unverzügliche Einleiten adä-quater Untersuchungen, um eine Sepsis durch z.…”
unclassified